Four Square Writing Method as A Technique to Teach Descriptive Writing - Abdul Muth’im; Norhasanah (JEELS (Journal of English Education and Linguistics Studies), 2018)
The objective of this study was to improve students’ skill in writing descriptive text utilizing Four Square Writing Method (FSWM). Thirty students of Junior High School participated in this classroom action research which took place in two cycles. Two sorts of instruments were used in this study; observation sheet and writing test. While the first was utilized to obtain the data on students’ responses and behavior, the latter was to achieve the data on students’ writing improvement. The implementation of the method in the first cycle was able to increase students’ mean score from 48.82 to 66.05. In the second cycle, more than 70% of the students successfully reached the score greater or equal to 72.95. This shows that the FSWM is one of alternative techniques in teaching descriptive text.